Peter Kalliney. Modernism in a Global Context. London: Bloomsbury, 2016. - Kevin C. Robbins (Studies in 20th & 21st Century Literature, 2018)
Review of Peter Kalliney. Modernism in a Global Context. London: Bloomsbury, 2016. 190 pp.
Keywords: Book Review; Peter Kalliney; Modernism in a Global Context